ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN SEKTOR PERBANKAN PERIODE 2016-2020 - Sahyunu, Sahyunu; Manan, La Ode ABdul; Aprianti, Resi (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2021)
This study aims to determine the influence of factors that affect the financial performance of the banking sector listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample in this study is 10 sample companies that meet the criteria for sampling. The analytical tool used is multiple linear regression analysis.The results of the study found that simultaneously CAR, NPL, BOPO and LDR had a positive and significant effect on financial performance. Partially CAR has a positive and significant effect on financial performance, NPL and BOPO have a negative and significant effect on financial performance and LDR has no significant positive effect on financial performance.